PEMETAAN PRODUKSI TANAMAN JAGUNG DI PROVINSI JAWA TENGAH DENGAN BERBASIS SISTEM INFORMASI GEOGRAFIS - Zahra Anggraeni Cattalya Putri Fahrul (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
Developing corn production is one aspect of agricultural development. This research for a Geographic Information System-based website was created with the aim of finding out data on corn production which fluctuated in 2017-2019 in Central Java Province. The data obtained was collected from related agencies such as BPS Central Java Province and the Ministry of Agriculture.